On some deep-sea Stenheliinae from the Gulf of California and the west coast of the Baja California Peninsula (Mexico): Pseudostenhelia bathyalis sp. nov., and Beatricella calidafornax sp. nov. (Copepoda: Harpacticoida: Miraciidae) - Gómez, Samuel (Zootaxa, 2021)
At present, only a handful of harpacticoid species of the families Ameiridae Boeck, Ancorabolidae Sars, Argestidae Por, and Rhizothrichidae Por have been described from the deep sea of the Gulf of California and west coast of the Baja California Peninsula. Recent efforts resulted in the description of a new genus, Wellstenvalia Gómez & Cruz-Barraza, 2021, closely related to Muohuysia Özdikmen, 2009 and Wellstenhelia Karanovic & Kim, 2014 and some new deep-sea species of Delavalia Brady, 1869. Other new stenheliin genera from the Gulf of California and the west coast of the Baja California Peninsula are the subjects of another contribution in this volume. The present contribution deals with the description of the first deep-sea representatives of Pseudostenhelia Wells, 1967 and Beatricella Scott, 1905, two typically shallow brackish water and marine genera. Some comments on their relationships are given.